Identification of distinct antigenic determinants on Semliki Forest virus by using monoclonal antibodies with different antiviral activities. - Boere, W A (1984)
Fifteen monoclonal antibodies (MAs) directed against either the E1 or E2 glycoprotein of Semliki Forest virus (SFV) were characterized by immunoglobulin subclass, pI traject, hemagglutination inhibition, neutralization of infectious virus, and protection against virulent infection in mice. All MAs except UM8.4 (immunoglobulin M [IgM]) belonged to various subclasses of IgG and predominantly to IgG2a, but all were unique as indicated by their banding patterns in isoelectric focusing. Competitive binding assays with these MAs revealed the presence of at least six distinct antigenic determinants (epitopes) on the E1 glycoprotein and five epitopes on the E2 glycoprotein. Two of the epitopes on E1, as defined by the properties of the MAs, were associated with hemagglutination inhibition (E1c and E1d), three were associated with neutralization (E1a, E1b, and E1f), and five were associated in various degrees with protection (E1a, E1b, E1c, E1e, and E1f) of mice against virulent SFV infection. With the MAs against E2, the epitopes on E2 were similarly defined. Epitopes E2b and E2e were associated with hemagglutination inhibition, E2c and E2d were associated with neutralization, and three epitopes were associated with in vivo protection (E2a, E2c, and E2d). Furthermore, for each MA the relative avidity to purified SFV was determined with an enzyme-linked immunosorbent assay. The binding of some MAs to purified SFV was enhanced by a second MA. The relative avidities of individual MAs did not correlate with their neutralizing capacities. From the results, we suggest that the amino acid sequence which makes up determinant E2d and is recognized by the highly protective MA UM5.1 is an excellent candidate for the production of a synthetic vaccine.